Acculturation strategy and language experience in expert ESL speakers: An exploratory study - Waniek-Klimczak, Ewa (Studies in Second Language Learning and Teaching, 2011)
Acculturation and language proficiency have been found to be inter-related both from the perspective of second language acquisition (Schumann, 1978, 1986) and socio-psychological adaptation in cross-cultural contacts (Ward, Bochner, & Furnham, 2001). However, the predictions as to the effect of a particular strategy on success differ, with assimilation believed to create most favourable conditions for SLA and integration for general well-being. The present study explores acculturation patterns in three expert users of English as a second language, recent Polish immigrants to the UK, in relation to their language experience. The qualitative data were collected with the use of a questionnaire and analysed with respect to language experience and socio-affective factors. The analysis aimed at better understanding of the relationship between language learning in a formal context and language use in a natural setting on the one hand and the relationship between language expertise and acculturation strategy choice on the other. The results show that in spite of individual differences, expert language users tend to adopt an assimilation rather than integration acculturation strategy. This may suggest that attitudes are related to expertise in English as a second language in a more conservative way than advocated by cross-cultural approaches.